2014
DOI: 10.1177/229255031402200302
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of the FlatWire Figure 8 sternal fixation device

Abstract: The FlatWire provides superior biomechanical properties compared with conventional steel wire, which may lead to reduced sternal wound complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The expanding prospective clinical trial aims to quantify sternal pain, patient risk factor stratification, operative duration, and postoperative complications in patients undergoing FlatWire closure in larger sample populations across other major institutions. Preliminary studies have shown FlatWires to provide superior biomechanical properties and less postoperative pain, characteristics known to reduce the incidence of post-sternotomy complications [7,8]. Further study of this new sternal closure device is warranted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expanding prospective clinical trial aims to quantify sternal pain, patient risk factor stratification, operative duration, and postoperative complications in patients undergoing FlatWire closure in larger sample populations across other major institutions. Preliminary studies have shown FlatWires to provide superior biomechanical properties and less postoperative pain, characteristics known to reduce the incidence of post-sternotomy complications [7,8]. Further study of this new sternal closure device is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…The median hospital costs for patients developing sternal wound complications following coronary bypass grafting (CABG) can be up to 2.8 times higher than for uncomplicated patients [7]. The Department of Health and Human Resources has identified these complications as hospital-acquired events for which hospitals should not receive additional payment if the condition was not present upon admission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation